Analysis of the backpack loading effects on the human gait - Machado, Leandro (2010)
Gait is a simple activity of daily life and one of the main abilities of the human being. Often during leisure, labour and sports activities, loads are carried over (e.g. backpack) during gait. These circumstantial loads can generate instability and increase biomechanical stress over the human tissues and systems, especially on the locomotor, balance and postural regulation systems. According to Wearing (2006), subjects that carry a transitory or intermittent load will be able to find relatively efficient solutions to compensate its effects. These are dependent upon the walking distance and of the load characteristics - size, weight and location relatively to the body (Hsiang, 2002).Thus, these solutions should become a concerning factor (Koh, 2009) and a topic of scientific research, particularly in what concerns the inventory of its biomechanical effects and the possible strategies to be developed in order to minimize its effects. The aim of the present study was to analyze the effects of an occasional dorso-lombar load during the gait through the use of a backpack.